Semi-continuous methane production from undiluted brown algae using a halophilic marine microbial community. (January 2016) - Miura, Toyokazu; Kita, Akihisa; Okamura, Yoshiko; Aki, Tsunehiro; Matsumura, Yukihiko; Tajima, Takahisa; Kato, Junichi; Nakashimada, Yutaka
Highlights: Acclimated marine sediment-derived culture was used for methanization of algae. Methane was produced continuously from equivalent of undiluted raw brown algae. Methane yield was above 300 mL/g VS at all organic loading rates (OLRs) tested. Hydrogenotrophic methanogens predominated among archaea during the highest OLR. Abstract: Acclimated marine sediment-derived culture was used for semi-continuous methane production from materials equivalent to raw brown algae, without dilution of salinity and without nutrient supply, under 3 consecutive conditions of varying organic loading rates (OLRs) and hydraulic retention time (HRT). Methane production was stable at 2.0 g VS/kg/day (39-day HRT); however, it became unstable at 2.9 g VS/kg/day (28-day HRT) due to acetate and propionate accumulation. OLR subsequently decreased to 1.7 g VS/kg/day (46-day HRT), stabilizing methane production beyond steady state. Methane yield was above 300 mL/g VS at all OLRs. These results indicated that the acclimated marine sediment culture was able to produce methane semi-continuously from raw brown algae without dilution and nutrient supply under steady state. Microbial community analysis suggested that hydrogenotrophic methanogens predominated among archaea during unstable methane production, implying a partial shift of the methanogenic pathway from acetoclastic methanogenesis to acetate oxidation.